Percolation Analysis of Brain Structural Network - Guo, Shu; Chen, Xiaoqi; Liu, Yimeng; Kang, Rui; Liu, Tao; Li, Daqing (Frontiers in Physics, 2021)
Brain network is one specific type of critical infrastructure networks, which supports the cognitive function of biological systems. With the importance of network reliability in system design, evaluation, operation and maintenance, we use the percolation methods of network reliability into brain networks and study the network resistance to disturbances and relevant failure modes. In this paper, we compare the brain networks of different species, including cat, fly, human, mouse, and macaque. The differences in structural features reflect the requirements for varying levels of functional specialization and integration, which determine the reliability of brain networks. In the percolation process, we apply different forms of disturbances to the brain networks based on metrics that characterize the network structure. Our findings suggest that the brain networks are mostly reliable against random or k-core based percolation with their structure design, yet becomes vulnerable under betweenness or degree-based percolation. Our results might be useful to identify and distinguish brain connectivity failures that have been shown related to brain disorders, as well as the reliability design of other technological networks.